Prognosis Implication of N-Terminal Pro-B-Type Natriuretic Peptide in Adult Patients With Acute Myocarditis - Zhao, Yan; Lyu, Naqiang; Zhang, Wei; Tan, Huiqiong; Jin, Qi; Dang, Aimin (Frontiers in Cardiovascular Medicine, 2022)
Background The aim of this study is to investigate the role of N-terminal pro-B-type natriuretic peptide (NT-proBNP) in assessing the poor outcomes of adult patients with acute myocarditis. Methods A total of 170 adult patients with available NT-proBNP information were included in the study. They were grouped according to quartiles of NT-proBNP concentrations at admission. Baseline and follow-up information was collected. Thirty-day major adverse cardiac events (MACE) were death and heart transplantation. Long-term MACE included all-cause death, heart transplantation, re-hospitalization due to heart failure, sustained ventricular arrhythmia, and myocarditis relapse. Results During a median follow-up of 3.8 years, patients in the highest NT-proBNP quartile suffered from the highest risk both of 30-day and long-term MACE (P < 0.001 by log-rank test). Multivariate analysis showed that apart from left ventricular ejection fraction (LVEF), an increased baseline NT-proBNP > 3,549 pg/mL (hazard ratio 3.535, 95% CI 1.316–9.499, P = 0.012) and NT-proBNP > 7,204 pg/mL (hazard ratio 22.261, 95% CI 1.976–250.723, P = 0.012) was independent predictor of long-term and 30-day MACE, respectively. Conclusions Higher baseline NT-proBNP level was an independent predictor of poor outcomes in adult patients with acute myocarditis. Therefore, NT-proBNP may serve as a useful biomarker for risk stratification in acute myocarditis patients.